Mechanisms of lipid regulation and lipid gating in TRPC channels. Issue 6 (June 2016) - Svobodova, Barbora; Groschner, Klaus
Graphical abstract: Highlights: Recent gain in understanding the lipid-sensing machinery of TRPC channels is provided based on available evidence from structural analysis of TRP complexes, homology modeling and functional analysis. Both qualitative and quantitative aspects of lipid sensing by TRPC channels are presented and a mechanistic concept of lipid-gating is discussed. Control of TRPC channels by complex lipid-protein interactions is discussed as a potential interface to cellular redox signaling. Abstract: TRPC proteins form cation channels that integrate and relay cellular signals by mechanisms involving lipid recognition and lipid-dependent gating. The lipohilic/amphiphilic molecules that function as cellular activators or modulators of TRPC proteins span a wide range of chemical structures. In this context, cellular redox balance is likely linked to the lipid recognition/gating features of TRPC channels. Both classical ligand-protein interactions as well as indirect and promiscuous sensory mechanisms have been proposed. Some of the recognition processes are suggested to involve ancillary lipid-binding scaffolds or regulators as well as dynamic protein–protein interactions determined by bilayer architecture. A complex interplay of protein–protein and protein-lipid interactions is likely to govern the gating and/or plasma membrane recruitment of TRPC channels, thereby providing a distinguished platform for signal integration and coincident signal detection. Both the primary molecular event(s) of lipid recognition by TRPC channels as well as the transformation of these events into distinct gating movements is poorly understood at the molecular level, and it remains elusive whether lipid sensing in TRPCs is conferred to a distinct sensor domain. Recent structural information on the molecular action of lipophilic activators in distantly related members of the TRP superfamily encourages speculations on TRPC gating mechanisms involved in lipid recognition/gating. This review aims to provide an update on the current understanding of the lipid–dependent control of TRPC channels with focus on the TRPC lipid sensing, signal-integration hub and a short discussion of potential links to redox signaling.